Integrating research : a guide for literature reviews - Cooper, Harris M. (London : Sage, 1989)
Includes statistics.
Rev. ed. of: The integrative research review / Harris M. Cooper. c1984.
Includes bibliographical reference and indexes.
Keywords: Social sciences -- Research; Research; Manuals; Data collection